‘Les anglicismes polluent la langue française’. Purist attitudes in France and Quebec - Walsh, Olivia (Cambridge University Press, 2014)
It is often claimed that France is a particularly purist country; the Acad´emie franc¸aise is seen to be representative of a purist outlook and popular works such as ´Etiemble’s attack on English influence Parlez vous franglais? (´Etiemble, 1964) have served to bolster this view. However, this claim has not been empirically verified. In order todetermine whether or not the rhetoric around purism in France matches the reality, we developed a questionnaire to investigate whether or not ordinary speakers of French in France are purist, taking the theoretical framework in George Thomas’s Linguistic Purism as a base (Thomas, 1991). This questionnaire was distributed online to a random sample of participants in France. To contextualise the findings, the questionnaire was also distributed to French speakers in Quebec. The results of the study show that, contrary to expectations, the French respondents display only mild purism and the Qu´eb´ecois respondents are more purist in the face of English borrowings (external purism). However, the French respondents are more concerned with the structure or ‘quality’ of the French language itself (internal purism) than their Qu´eb´ecois counterparts. This study also highlights some problems with Thomas’s framework, which requires some modification for future research.